P382 Scalp fungal microbiome and sebum composition in males with and without androgenetic alopecia. (20th September 2022) - Sugita, Takashi; Suzuki, Kazuhiro; Cho, Otomi
Abstract: Poster session 3, September 23, 2022, 12:30 PM - 1:30 PM:   Objects: Lipophilic Malassezia species are abundant in the scalp microbiome; we investigated the scalp microbiome and sebum composition of patients with androgenic alopecia (AGA) and aimed to identify factors accelerating AGA progression. Materials and Methods: Scalp scale samples (swabs) were collected from 55 male Japanese patients with AGA and 63 healthy individuals. Fungal rRNA genes were amplified by PCR and the amplicons were sequenced on the MiSeq platform. The extent of fungal colonization was determined by qPCR. We used gas chromatography/mass spectrometry to measure the sebum levels of free fatty acids, diglycerides, triglycerides, squalene, free cholesterol, cholesterol esters, and wax. Results and Discussion: Malassezia restricta predominated in all AGA (64.7%) and non-AGA age groups (44.6%). qPCR revealed that Malassezia colonization was more extensive in the AGA than non-AGA group, regardless of age; the Malassezia level was significantly higher in ADA subjects aged 50–59 than 30-49 years. The TG level was significantly higher in the AGA than non-AGA group ( P  <.05), but the free fatty acid, squalene, and free cholesterol levels were significantly lower (all P  <.05). Conclusion: Thus, the scalp fungal microbiome and sebum composition may influence AGA development.